PROVERBS IN MARTIN AMIS’S LONDON FIELDS - Maja Gwóźdź (Proverbium, 2016)
The aim of this paper is to present how Martin Amis uses proverbs in order to achieve a particular stylistic effect. The study draws on the corpus of 18 proverbs identified in London Fields of which paremias used in the canonical form represent precisely 50%. The findings show that the most qualitatively considerable alteration of proverbial structure includes changes in terms of lexical substitution. Examples are provided in order to examine the hypothesis that the proverbs altered by means of lexical substitution display polemics with traditional wisdom, whereas adages used in the canonical form are an attempt to re-evaluate proverbial truths. It has been observed that the use of structural changes or canonical forms has a different value for a given discourse. As regards the methodological tools used in this study, the analysis of proverbs with different paradigmatic relations and their literary relevance is largely based on the semiotic commutation test and the systemic-functional grammar approach applied as a component of discourse analysis. In particular, the transitivity theory proposed by M.A.K. Halliday is used to investigate the semantic links between proverbs and discourse. The conclusions drawn from this analysis may be further used for stating that Martin Amis’s novel displays a high level of stylistic dexterity as regards the use of proverbs to suit literary purposes.